Controlling as a Asupporttool for Generating Savings in Procurement - Dudić, Željko (International Journal of Industrial Engineering and Management, 2015)
Procurement controlling process increases efficiency and reduces costs associated with improperly submitted orders. Most large organizations already appreciate the advantage to be advised by effectively controlling purchasing activities. Procurement controlling and procurement performance management are two synonyms for the same functional area. Through procurement controlling purchases received information that is relevant for their purchasing decision. Improving supplier performance is a challenge faced by many organizations, accordingly this, procurement controlling offers the right tools such as developing balanced scorecard. By developing a set of a leading performance measures, managers have the information necessary to identify opportunities for performance improvement. Article history: Received (12.11.2015); Revised (20.12.2015); Accepted (29.12.2015)